Case Report: Stereoelectroencephalography and Stereoelectroencephalography-Guided Radiofrequency Thermocoagulation in Familial Lateral Temporal Lobe Epilepsy - Wei, Ziqi; Ye, Xiaolai; Wang, Changquan; Xu, Jiwen; Zhang, Puming; Liu, Qiangqiang; Zhao, Jun (Frontiers in Neurology, 2022)
Familial lateral temporal lobe epilepsy (FLTLE) or autosomal dominant lateral temporal epilepsy (ADLTE) is a genetic focal epilepsy usually characterized by auditory symptoms. Most FLTLE seizures can be controlled by drugs, and to our best knowledge, there are no previous reports about stereoelectroencephalography (SEEG) used for FLTLE patients. In this report, we present two FLTLE patients in one family and their SEEG performances together with 18F-FDG PET and MRI results. In case 1, abnormality activity originated from the right superior temporal gyrus and spread rapidly to the right insular lobe and hippocampus. In case 2, there were two seizure patterns: (1) Fast activity emission or slow complex waves were identified at the left superior temporal gyrus followed by sharp wave and spike wave recruitments. (2) Fast activities and slow wave oscillation and fast activities were identified at left superior temporal gyrus recruitment, and finally spread to other electrodes. SEEG-guided radiofrequency thermocoagulation was performed for both patients and one of them underwent resection surgery. Seizures are well controlled and the patients are very satisfied with the therapeutic effects.